Right Truncated Shankar Distribution and its Properties - Bayda Atiya Kalaf; Sairan Hamza Raheem; Feras Sh. M. Batah (Ibn Al-Haitham Journal for Pure and Applied Sciences)
Since the importance of truncated distributions has increased in many scientific fields in recent years and they provide valuable insights when dealing with censored or truncated data, this paper presents the Right Truncated Shanker Distribution as a new statistical distribution developed for modelling right truncated data. The distribution is defined by specifying its probability density function and cumulative distribution function under the truncation condition, the survival function and the hazard function. In addition, some properties of the right truncated Shanker distribution are derived, such as the moments around the origin, the variance, the coefficients of skewness and kurtosis, the moment generating function, and the mean time to failure. Our statistical properties show that the new distribution has the utility and flexibility to effectively model truncated data scenarios.